2016
DOI: 10.5395/rde.2016.41.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of canal transportation in simulated curved canals prepared with ProTaper Universal and ProTaper Gold systems

Abstract: ObjectivesThe purpose of this study was to assess the ability of ProTaper Gold (PTG, Dentsply Maillefer) in maintaining the original profile of root canal anatomy. For that, ProTaper Universal (PTU, Dentsply Maillefer) was used as reference techniques for comparison.Materials and MethodsTwenty simulated curved canals manufactured in clear resin blocks were randomly assigned to 2 groups (n = 10) according to the system used for canal instrumentation: PTU and PTG groups, upto F2 files (25/0.08). Color stereomicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…All canals were produced with a 0.15 mm apical foramen, 0.02 taper, 16.5 mm canal length, a 60°curvature (4.5 mm radius) and a 10-mm straight section before the curve [16]. Subsequently, the blocks were randomly assigned to 3 groups (n = 10): PTU, Reciproc and K3XF.…”
Section: Methodsmentioning
confidence: 99%
“…All canals were produced with a 0.15 mm apical foramen, 0.02 taper, 16.5 mm canal length, a 60°curvature (4.5 mm radius) and a 10-mm straight section before the curve [16]. Subsequently, the blocks were randomly assigned to 3 groups (n = 10): PTU, Reciproc and K3XF.…”
Section: Methodsmentioning
confidence: 99%
“…All four Gold and Blue heat‐treated NiTi systems create well‐centred preparation even in severely curved root canals (Elnaghy & Elsaka , Silva et al . , Duque et al . , Özyürek et al .…”
Section: Martensitic Niti Alloymentioning
confidence: 99%
“…A study examining canal transportation in simulated curved canals prepared with PTU and PTG showed that these two systems produced similar canal transportation in the straight part of the canal. 25 In the curved part, however, Silva et al found that the PTG system produced overall less canal transportation when compared with the PTU system. This finding contrasts with a study that showed PTG and PTU as having similar root canal shaping abilities in the preparation of mesial canals of mandibular first molars.…”
Section: Protaper Gold (Dentsply Sirona)mentioning
confidence: 99%
“…TRUShape 3D Conforming Files (TRS) (Dentsply Tulsa Dental Specialties, Tulsa, OK, USA) ( Figure 10) were launched in 2015 in four available sizes (20,25,30,40), each with a variable regressive 6% taper to a maximum flute diameter of 0.80 mm.…”
Section: A Smooth Transition Between Instruments Because Of a Design mentioning
confidence: 99%
See 1 more Smart Citation